Regulasi diri belajar dan mindfulness: Dapatkah menjadi prediktor prokrastinasi akademik mahasiswa? - Riestanti Dias Puspita; Suhadianto (INNER: Journal of Psychological Research, 2021)
Abstract This study aims to determine: 1) the negative relationship between learning self-regulation and academic procrastination in students, 2) the negative relationship between mindfulness and academic procrastination in students. Participants in this study were students of the eighth-semester students of the Faculty of Psychology, University of August 1945 Surabaya, totaling 125 students. The instrument in this study used the academic procrastination scale, the learning self-regulation scale, and the mindfulness scale compiled by the researcher. The results of data analysis using Spearman's Rho correlation showed 1) there was a very significant negative relationship between self-regulation of learning and academic procrastination (ρ = -0,774 / Sig. 0,000); 2) there is a significant negative relationship between mindfulness and academic procrastination (ρ = -0,501 / Sig. 0,000). The conclusion is that the higher the self-regulation of learning and the mindfulness of students, the lower the academic procrastination. Keywords: Self-Regulation in Learning; Mindfulness; Academic Procrastination Abstrak Penelitian ini bertujuan untuk mengetahui: 1) hubungan negatif antara regulasi diri belajar dengan prokrastinasi akademik pada mahasiswa, 2) hubungan negatif antara mindfulness dengan prokrastinasi akademik pada mahasiswa. Partisipan dalam penelitian ini adalah mahasiswa Fakultas Psikologi Universitas 17 Agustus 1945 Surabaya semester delapan yang berjumlah 125 mahasiswa. Instrumen dalam penelitian ini menggunakan skala prokrastinasi akademik, skala regulasi diri belajar dan skala mindfulness yang disusun oleh peneliti. Hasil analisis data menggunakan korelasi Spearman’s Rho menunjukkan 1) terdapat hubungan negatif yang sangat signifikan antara regulasi diri belajar dengan prokrastinasi akademik (ρ =-0,774/Sig. 0,000); 2) terdapat hubungan negatif yang cukup signifikan antara mindfulness dengan prokrastinasi akademik (ρ =-0,501/Sig. 0,000). Kesimpulannya adalah semakin tinggi regulasi diri belajar dan mindfulness mahasiswa akan semakin rendah prokrastinasi akademik. Kata kunci: Regulasi Diri Belajar; Mindfulness; Prokrastinasi Akademik